Investigating membrane materials for sustainable hydrogen production from biomass for use in the energy sector - DINCĂ, Cristian; STAN, Ioana-Simina; BADEA, Adrian (Annals of the Academy of Romanian Scientists. Series on engineering sciences, 2024)
The study explores the potential of membrane materials in sustainable hydrogen production from biomass, focusing on their utilization in the energy sector. Integrating advanced membrane technologies aims to optimize biomass conversion processes into hydrogen without CO2 emissions. The analysis focuses on the selectivity and permeability characteristics of different membranes, evaluating the efficiency and sustainability of the process. Using resulting hydrogen in the energy sector can reduce dependence on fossil energy sources and promote a cleaner, more sustainable economy.